Synthesis, Spectral Studies and Antibacterial Activity of Rare-Earth Metal Complexes with 1-Hydroxy-1-Phenyl. 3-Allyl-2-Thiourea. - SWAMI, V.K.; MATHUR., S.P. (Asian Journal of Chemistry, 2010)
In the present work, the synthesis, spectral and antibacterial activity of rare-earth metal complexes with substituted thiourea are reported.